The Use of Therapeutic Ultrasound in the Management of Patients with Temporomandibular Disorder: A Clinical, Cross-Sectional and Quantitative Study - , Iza Melo Freitas, Carlos Ricardo de Queiroz Martiniano, Marcelo Bruno Lemos de Oliveira, Thereza Cristina Farias Botelho Dantas, Patrícia Lenora dos Santos Braga, Emmanuel Arraes de Alencar Júnior, Antônio Sérgio Guimarães (Archives of Current Research International, 2025)
Background: To manage the temporomandibular disorders (TMD), one of the resources used is therapeutic ultrasound (UST). Objective: To evaluate the use of therapeutic ultrasound in individuals with temporomandibular disorders (TMD). Methods: This is a clinical study, which 42 individuals,aged 18-73 years, diagnosed with TMD were recruited. Participants then bit into a wooden spacer until they felt fatigue in the masseter muscle, with time assessed on both sides(right and left), followed by chewing gum. Subsequently,USD was applied to the masseter (at a frequency of 2.0 W=0.52W/cm² for 4 minutes) and the wooden spacer test was repeated to assess the time of fatigue in this muscle. Results: The most affected age group was up to 28 years old (52.4%), and females (73.8%) (p<0.05). Regarding the amount of fatigue, there was a decrease on the left side in the control group and on both sides in the TMD group, with a significant difference (P=0.0049) for the left side when evaluating before and after the treatment.When comparing times, the TMD group also showed the greatest reduction, (P=0.0012) for the left side. Conclusion: It is concluded that ultrasound therapy promoted immediate improvement in the tightening of the wooden spacer,causing muscle relaxation through the heat applied,reducing fatigue in the masseter muscle.